2018
DOI: 10.3389/fpsyt.2018.00425
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Ethanol Exposure in Adolescent Rats Causes Residual Alterations in Endogenous Opioid Peptides

Abstract: Adolescent binge drinking is associated with an increased risk of substance use disorder, but how ethanol affects the central levels of endogenous opioid peptides is still not thoroughly investigated. The aim of this study was to examine the effect of repeated episodic ethanol exposure during adolescence on the tissue levels of three different endogenous opioid peptides in rats. Outbred Wistar rats received orogastric (i.e., gavage) ethanol for three consecutive days per week between 4 and 9 weeks of age. At 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…These findings raise the possibility that the diminished -endorphin release in the NAc may be attributed to suppression of endorphinergic input to the NAc during withdrawal from chronic ethanol. Similarly, it has been shown that NAc -endorphin levels in the ethanolintoxicated state were significantly decreased compared with waterintoxicated state (30). As hypothalamic endorphinergic neurons innervate the NAc (10), the decreased -endorphinergic neuron activity during ethanol withdrawal would result in the excitation of NAc GABA neurons in the NAc.…”
Section: Discussionmentioning
confidence: 93%
“…These findings raise the possibility that the diminished -endorphin release in the NAc may be attributed to suppression of endorphinergic input to the NAc during withdrawal from chronic ethanol. Similarly, it has been shown that NAc -endorphin levels in the ethanolintoxicated state were significantly decreased compared with waterintoxicated state (30). As hypothalamic endorphinergic neurons innervate the NAc (10), the decreased -endorphinergic neuron activity during ethanol withdrawal would result in the excitation of NAc GABA neurons in the NAc.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, the present study differs from the work described above in that our electrophysiological testing occurred after a protracted abstinence period, rather than during acute withdrawal. Studies examining changes to expression of the KOR system have found that dynorphin-B peptide levels were upregulated 21 days following adolescent alcohol exposure (Granholm, Segerstrom, & Nylander, 2018;Lindholm, Ploj, Franck, & Nylander, 2000), but current studies examining long-term changes to KOR function following chronic alcohol exposure are limited. One study examining the role of the KOR system in the alcohol deprivation effect following 18 days of abstinence found that the selective KOR antagonist JDTic reduced the reinstatement of alcohol intake (Uhari-Väänänen et al, 2019), while another found that the KOR system was still actively involved in mediating abstinence-induced stress responsiveness six weeks after chronic alcohol exposure (Gillett, Harshberger, & Valdez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As for the effects of ethanol on brain function, it activates various receptors and ion channels through several neurotransmitter networks, including the endogenous opioid system (Söderpalm & Ericson, 2011; Trigo et al, 2010). In this respect, there is evidence indicating that episodic exposure of adolescent rats with ethanol alters the level of opioid peptides (dynorphin, B-endorphin, and met-enkephalin) in specific regions underlying pain modulation (Granholm et al, 2018). It is noteworthy that these changes were found to be persistent in some brain areas, such as amygdala, hypothalamus, and pituitary, which may somehow explain the future vulnerability for opioid effect (Granholm et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, there is evidence indicating that episodic exposure of adolescent rats with ethanol alters the level of opioid peptides (dynorphin, B-endorphin, and met-enkephalin) in specific regions underlying pain modulation (Granholm et al, 2018). It is noteworthy that these changes were found to be persistent in some brain areas, such as amygdala, hypothalamus, and pituitary, which may somehow explain the future vulnerability for opioid effect (Granholm et al, 2018). These findings raise a possibility that alteration of opioid levels in specific structures may promote the development of analgesic tolerance at cellular levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation